Socio- Economic Impact of Khat Addiction on the Family Wellbeing in Dire Dawa City in Particular in Sub-City of Sabean - Tufa Telila, Shambel (IJRDO - Journal of Social Science and Humanities Research, 2017)
The main purpose of this research is to investigate the socio-economic impact ofkhat addiction on well-being family among peoples of Dire Dawa particularly in the Sub- city of Sabean. Ethiopians especially the people of Dire Dawa has experienced chewing Khat for a long period of time. They had been socially and culturally on emphasizing of chewing Khat and an unaware about the impact of khat on family wellbeing less recognized the prevalence of consumption, and existing dominant discourse on family.